Susan Stitkevich’s Approach to Ancient Arabic Literature: A Descriptive Study on Selected Samples - Mahmoud Miqdadi, Dr. Ziyad (Al-Adab Journal, 2020)
This research deal with some studies carried out by the Orientalist Susan Stitkevich of the ancient Arabic literary text, which constituted a major field of study for Arab scholars and Orientalists. The study arises many findings among which: There is a strong relationship between the ancient Arab literary text and other cultures that are interested in it, some Western critical theories can be applied to ancient Arab literature, the critical efforts of Orientalist Susan Stitkevich are of great importance in the study of the ancient Arabic text, these studies have an impact on the presentation of new meanings, which confirms the vitality and continuity of this literature, there are some drawbacks to the approach of the Orientalist Susan Stitkevich in its preview of the ancient Arabic literary text. The study provides a number of recommendations among which: the necessity of taking care of the orientalist studies that conducted on the old Arabic literary text, taking care of it to benefit from the results, introducing orientalist studies and informing the specialists, especially graduate students in the Arab universities, the need to examine these studies and follow them and critique scientific criticism to show the merits and shortcomings.